Road humps: accident prevention or hazard?. Issue 4 (July 1996) - Bowrey, D; Thomas, R; Evans, R; Richmond, P
Abstract : Two cases of injury to passengers seated on public transport buses occurred after the vehicles had traversed road humps. While the potential dangers to seated bus passengers have been acknowledged in the Department of Transport literature, specific mention in medical reports is lacking. Should the United Kingdom follow the example set by the United States, where the placement of road humps on bus routes is avoided?